Hair analysis for beta‐blockers and calcium‐channel blockers by using liquid chromatography‐tandem mass spectrometry as a tool for monitoring adherence to antihypertensive therapy. Issue 10 (21st July 2022) - Taus, Francesco; Gottardo, Rossella; Ballotari, Marco; Utzeri, Chiara; Tagliaro, Franco
Abstract: Adherence to therapy is the key to a successful therapeutic intervention, especially in cardiovascular diseases in which a lack of adherence may have serious consequences in terms morbidity and/or mortality. In this context, hair analysis can be an excellent tool to monitor adherence to therapy. Indeed, drugs present in blood are incorporated into the hair matrix, where drugs and metabolites can stay unaltered for a long time protected from metabolism and degradation. In the present study, a simple, specific, and sensitive ultra‐high performance liquid‐chromatography–tandem mass spectrometry (UHPLC‐MS/MS) method set up to determine in human hair seven beta‐blockers (viz., metoprolol, sotalol, labetalol, atenolol, nebivolol, bisoprolol, and nadolol) and two calcium‐channel blockers (lercanidipine and amlodipine), which are widely prescribed to treat medium‐to‐severe hypertensive conditions. The optimized method was successfully validated in terms of accuracy, repeatability, reproducibility, matrix effect and extraction recovery. Moreover, the applicability of the method was evaluated by analyzing 34 real samples of hair obtained from patients under long‐term therapy with calcium channel blockers and beta‐blockers. Abstract : The present work aimed at verifying the possibility to use liquid chromatography coupled with mass spectrometry to quantitatively determine antihypertensive drugs in the hair of subjects undergoing chronic treatments. The study includes seven beta‐blockers (viz., atenolol, bisoprolol, labetalol, metoprolol, sotalol, nebivolol, and nadolol) and two calcium channel blockers (amlodipine and lercanidipine). The practical applicability of the method was also verified by analyzing 34 authentic hair samples collected from subjects under chronic therapy with those cardiovascular drugs.